The Effect of Customer Orientation and Service Quality on Customer Loyalty Mediated by Customer Satisfaction at Bank BRI - Lamtiur Sihombing; Muhammad Arief; Ika Baskara; Gilang Pratama Hafids (Neo Journal of economy and social humanities, 2025)
This research aims to explore the influence of service quality and customer orientation on customer loyalty through customer satisfaction at Bank BRI in Bekasi City. Using a descriptive quantitative approach, data were collected from 105 respondents via an online questionnaire and analyzed using Structural Equation Modeling – Partial Least Square (PLS-SEM). The analysis results indicate that service quality and customer orientation do not have a direct significant effect on customer loyalty. However, service quality has a significant positive impact on customer satisfaction, which ultimately enhances customer loyalty. Customer orientation also positively influences customer satisfaction, but it does not have a statistically significant impact on customer loyalty through customer satisfaction. These findings highlight the importance of customer satisfaction as a mediator linking service quality to customer loyalty. The managerial implications for Bank BRI include the need to improve service quality and customer orientation to enhance customer satisfaction and loyalty. Future research is recommended to involve a larger sample size, utilize diverse research methods, and consider external factors such as policy changes or economic conditions that may influence customer perceptions. The results of this study provide valuable insights for developing more effective service strategies and customer retention efforts in the future.